2016
DOI: 10.3892/ol.2016.5240
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of AKR1B10 gene expression in hepatocellular carcinoma and surrounding non-tumorous liver tissue

Abstract: Abstract. When assessing outcome in hepatocellular carcinoma (HCC), it is important to consider prognostic factors in background non-tumorous liver tissue as well as in the tumor, since multiple occurrence is associated with background liver status such as hepatitis. The current study aimed to elucidate molecular prognostic predictors that have an association with HCC background non-tumorous tissue. Microarray expression profiling identified aldo-keto reductase family 1, member B10 (AKR1B10) as a putative non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
(32 reference statements)
2
16
0
Order By: Relevance
“…A prevalent serum marker would improve clinical management of HCC. Secretory AKR1B10 protein is overexpressed in HCC, (14,25) and studies on surgical specimens and clinicopathological data indicated its potential as a marker for early-stage HCC, (32,33) prognosis, (27,34,35) BLT discrimination, (26) and stratification of HCC risk in liver hepatitis B virus and hepatitis C virus infections. (36)(37)(38)(39) These studies of AKR1B10 in HCC pave the road for this large-scale multicenter serological study for detection of HCC, including early-stage HCC and AFP-negative HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalent serum marker would improve clinical management of HCC. Secretory AKR1B10 protein is overexpressed in HCC, (14,25) and studies on surgical specimens and clinicopathological data indicated its potential as a marker for early-stage HCC, (32,33) prognosis, (27,34,35) BLT discrimination, (26) and stratification of HCC risk in liver hepatitis B virus and hepatitis C virus infections. (36)(37)(38)(39) These studies of AKR1B10 in HCC pave the road for this large-scale multicenter serological study for detection of HCC, including early-stage HCC and AFP-negative HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Sonohara et al . reported that the ratio of AKR1B10 messenger RNA levels in HCC and corresponding non‐tumorous tissues may predict prognosis after curative hepatectomy, with low expression in HCC tissue relative to non‐tumorous tissue indicative of poor prognosis . Yoshitake et al .…”
Section: Discussionmentioning
confidence: 99%
“…The AKR1B10 gene encodes a member of the AKR superfamily . Human AKR1B10 is reported to be overexpressed in several human cancers, including lung and liver cancers . AKR1B10 is often overexpressed in male and smoking NSCLC patients, therefore AKR1B10 has been proposed as a diagnostic marker in smokers with NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…After full-text review, 12 articles were excluded. Eventually, we identi ed 11 articles published between 2014 and 2019, which were included in the nal analysis [5][6][7][8][9][10][11][12][13][14][15]. The ow diagram of the literature search is shown in Fig1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies have shown that AKR1B10 is characterized by obvious carcinogenicity and can be used as a tumor marker [4]. Recently, an increasing number of studies showed that abnormal expression of AKR1B10 is signi cantly correlated with the prognosis of certain solid tumors [5][6][7][8][9][10][11][12][13][14][15]. However, the currently available results are inconsistent, and the prognostic value of AKR1B10 remains unclear.…”
Section: Introductionmentioning
confidence: 99%